2021
DOI: 10.1038/s41398-020-01189-3
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic effects of NLRP3 inflammasome inhibition in a model of chronic sleep deprivation

Abstract: Sleep deprivation is a form of stress that provokes both inflammatory responses and neuropsychiatric disorders. Because persistent inflammation is implicated as a physiological process in anxiety disorders, we investigated the contributions of NLRP3 inflammasome signaling to anxiety and anxiolytic properties of flavanol diets in a model of chronic sleep deprivation. The results show a flavanol-rich dietary preparation (FDP) exhibits anxiolytic properties by attenuating markers of neuroimmune activation, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 82 publications
0
19
0
1
Order By: Relevance
“…It is important to note that neuro-immune and nitro-oxidative toxicity play a key role in the pathophysiology of chronic fatigue syndrome (CFS), major depression (MDD), and generalized anxiety disorder (GAD) (Maes, Bonifacio et al 2018, Maes and Carvalho 2018, Almulla and Maes 2022, Maes, Kubera et al 2022). There is now also evidence that upregulation of the NLRP3 inflammasome plays a key role in MDD (Kaufmann, Costa et al 2017, Zhou, Fernando et al 2021), fatigue (Zhang, Du et al 2016, Zhang, Ma et al 2017), cognitive impairments (Kuwar, Rolfe et al 2021), and anxiety (Aghaie, Moradifar et al 2021, Smith, Trageser et al 2021). Nevertheless, there are no data whether the NLRP3 inflammasome and lowered Ca are involved in the physio-affective phenome of Long COVID.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that neuro-immune and nitro-oxidative toxicity play a key role in the pathophysiology of chronic fatigue syndrome (CFS), major depression (MDD), and generalized anxiety disorder (GAD) (Maes, Bonifacio et al 2018, Maes and Carvalho 2018, Almulla and Maes 2022, Maes, Kubera et al 2022). There is now also evidence that upregulation of the NLRP3 inflammasome plays a key role in MDD (Kaufmann, Costa et al 2017, Zhou, Fernando et al 2021), fatigue (Zhang, Du et al 2016, Zhang, Ma et al 2017), cognitive impairments (Kuwar, Rolfe et al 2021), and anxiety (Aghaie, Moradifar et al 2021, Smith, Trageser et al 2021). Nevertheless, there are no data whether the NLRP3 inflammasome and lowered Ca are involved in the physio-affective phenome of Long COVID.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, IL-1β activity shows a bidirectional relationship with the circadian timing system. The biological clock controls IL-1β secretion in diverse tissues and immune cells, and when circadian rhythms are disrupted the inflammatory processes worsen in various medical conditions involving IL-1β signaling ( Pourcet and Duez, 2020 ), also leading to behavioral consequences in animal models ( Smith et al, 2021 ). On the other hand, IL-1β regulates sleep by acting on monoaminergic neurotransmission ( Imeri and Opp, 2009 ) and specific neuronal receptors ( Davis et al, 2015 ), and the disruption of the circadian rhythmicity of brain homeostatic mechanisms and inflammatory signaling has been proposed as a pathogenetic mechanism in mood disorders, which involve a marked disruption of all circadian mechanisms ( Wirz-Justice and Benedetti, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SD increases cytokine production, microglial activation and initiates neuronal apoptosis, causing lesions in the hippocampus of mice (68,69). Interestingly PDE4 expression is regulated by inflammation and microglial reactivity (70).…”
Section: Discussionmentioning
confidence: 99%
“…Further, cresyl violet staining showed neuronal death in the hippocampus region of SD mice. Recent studies have shown that SD increases cytokine production, and microglial activation and initiates neuronal apoptosis, causing lesions in the hippocampus of mice 63, 64 . Increased PDE4B expression is reported to trigger inflammation and microglial reactivity 65 .…”
Section: Discussionmentioning
confidence: 99%